2015
DOI: 10.1590/0103-8478cr20130906
|View full text |Cite
|
Sign up to set email alerts
|

Germinação sob altas temperaturas para avaliação do potencial fisiológico de sementes de milho

Abstract: RESUMO O objetivo do trabalho foi avaliar e padronizar o teste de germinação sob altas temperaturas para avaliação do vigor de sementes de milho. Foram utilizados seis lotes de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
2
Order By: Relevance
“…Although 25 ºC is not considered a low temperature for germination in maize seeds, and is suggested when carrying out the standard germination test (BRASIL, 2009), using a temperature of 30 ºC may have resulted in greater dry-weight accumulation in the purple maize seedlings due to favouring greater speed in the germination process (Figure 2B). When studying different maize batches, Sbrussi and Zucareli (2015) found that a temperature of 34 ºC gave the greatest dry weight accumulation for both the shoots and root system of maize seedlings.…”
Section: Resultsmentioning
confidence: 99%
“…Although 25 ºC is not considered a low temperature for germination in maize seeds, and is suggested when carrying out the standard germination test (BRASIL, 2009), using a temperature of 30 ºC may have resulted in greater dry-weight accumulation in the purple maize seedlings due to favouring greater speed in the germination process (Figure 2B). When studying different maize batches, Sbrussi and Zucareli (2015) found that a temperature of 34 ºC gave the greatest dry weight accumulation for both the shoots and root system of maize seedlings.…”
Section: Resultsmentioning
confidence: 99%
“…2) and the smallest value of β2 of inclination of the quadratic regression model when subjected to higher temperatures, (0.19), being then considered the seeds with greater force. The tolerance for above-average temperatures can pose a direct relationship with the plant's performance on the field, this factor can then be used efficiently as a test for the assessment of seed vigor [32].…”
Section: Resultsmentioning
confidence: 99%
“…(2015), que, avaliando o efeito da temperatura no comportamento de germinação de milho branco, amarelo, roxo e vermelho, observaram que a temperatura para o milho apresentar melhor comportamento está na faixa dos 30ºC, demonstrando, assim como no presente estudo, que as temperaturas baixas de 15ºC e as elevadas de 40°C, provocam retardo na germinação das sementes, quando comparadas à faixa intermediária. Sbrussi & Zucareli (2015), avaliando a qualidade fisiológica de sementes de milho germinadas em altas temperaturas também mostraram decréscimo na germinação de sementes submetidas a temperaturas superiores a 34ºC.…”
Section: Discussionunclassified